SADC Strategies to Overcome Religion-Inspired Conflicts In the Region: An Intellectual Peek From the SADC Mission in Mozambique - Tabinga, Vengai; Gwite, Douglas (Lighthouse: The Zimbabwe Ezekiel Guti University Journal of Law, Economics and Public Policy, 2025)
The study critically evaluates the strategies aimed at ameliorating or overcoming religious-inspired conflicts in the Southern African Development Community (SADC) region using the Cabo Delgado conflict in Northern Mozambique as a case study. The study and thrust stems from the background that Africa has been struggling to bring about positive peace in religion-motivated conflicts. What is known is that the African Union Peace and Security Architecture (APSA) and its regional subordinate organs, such as the SADC Organ on Politics Defence and Security. do have conflict prevention strategies. However, missing in critical analysis is the efficacy of these strategies, given the enduring nature of religious motivated conflicts. The main strand permeating this research is the inquiry contributing to the continued escalation of the Cabo Delgado conflict in the presence of SADC conflict management strategies. The study is informed by interpretivism theoretical and methodological paradigms. It adopts a qualitative approach and uses online interviews to collect data from the SADC Mission in Mozambique (SAMIM) troops deployed in Pemba, Macomia, Muidumbe and Nagande. The major finding from the study is that the SADC does not have a doctrine that specifically responds to religion-inspired conflicts. There is poor response mechanisms when early warning about conflicts is given. The failure of SADC to prevent and resolve the conflict is also attributable to the Mozambican government‘s inability to respond to the African Peer Review Mechanism (APRM) warning of the conflict. The article recommends that SADC come up with a Counter Religion-Inspired Insurgence Doctrine (CRIID).